Interpreting elections - Kelley, Stanley (Princeton University Press, 1983)
Stanley Kelley, Jr., offers a new way of interpreting election outcomes without relying on the kind of arbitrary speculation usually elicited by this and other questions. He examines presidential elections from 1952 to 1981), with emphasis on the Johnson and Nixon landslides. Originally published in 1983. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original texts of these important books while presenting them in durable paperback editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.